Diverse Control Mechanisms of the Interleukin-1 Cytokine Family - Evavold, Charles L.; Kagan, Jonathan C. (Frontiers in Cell and Developmental Biology, 2022)
The majority of interleukin-1 (IL-1) family cytokines lack amino terminal secretion signals or transmembrane domains for secretion along the conventional biosynthetic pathway. Yet, these factors must be translocated from the cytoplasm across the plasma membrane into the extracellular space in order to regulate inflammation. Recent work has identified an array of mechanisms by which IL-1 family cytokines can be released into the extracellular space, with supramolecular organizing centers known as inflammasomes serving as dominant drivers of this process. In this review, we discuss current knowledge of the mechanisms of IL-1 family cytokine synthesis, processing, and release from cells. Using this knowledge, we propose a model whereby host metabolic state dictates the route of IL-1β secretion, with implications for microbial infection and sterile inflammation.